2003
DOI: 10.1002/cncr.11145
|View full text |Cite
|
Sign up to set email alerts
|

Electronic support groups for breast carcinoma

Abstract: BACKGROUNDA recent Pew Charitable Trust study found that 52,000,000 individuals used the Internet to obtain health/medical information. Clinical trials of face‐to‐face breast carcinoma support groups show evidence of 1) improvement in quality of life, 2) reduction of psychologic symptoms, 3) improvement in coping responses, and 4) a reduction in pain. To the authors' knowledge, a few studies published to date have investigated Internet‐delivered electronic support groups (ESGs) for cancer. The most sophisticat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
141
2
8

Year Published

2004
2004
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(159 citation statements)
references
References 15 publications
8
141
2
8
Order By: Relevance
“…This was evidenced by participants' descriptions of how the anonymous nature of online support groups allowed them to express themselves more openly and receive more honest responses from other members. Our findings are consistent with previous research which has shown that online support groups serve as a useful venue where members can both offer and receive emotional support (Bar-Lev, 2008;Han, et al, 2008;Lieberman et al, 2003).…”
Section: Empowering Processes Within Online Support Groupssupporting
confidence: 93%
“…This was evidenced by participants' descriptions of how the anonymous nature of online support groups allowed them to express themselves more openly and receive more honest responses from other members. Our findings are consistent with previous research which has shown that online support groups serve as a useful venue where members can both offer and receive emotional support (Bar-Lev, 2008;Han, et al, 2008;Lieberman et al, 2003).…”
Section: Empowering Processes Within Online Support Groupssupporting
confidence: 93%
“…That finding challenges a belief held by many health care professionals that Internet-based social relationships are inherently superficial, tenuous, and lacking commitment 31,37 . Participation rates in online groups vary and can be low, but participation rates in our osgs were comparable or better than have been reported for other online group interventions 26,38,39 and for other face-to-face group interventions 13 . Participants communicated absences (which were usually of a medical nature) and described unexpectedly strong feelings of kinship toward their fellow osg members.…”
Section: Discussionsupporting
confidence: 67%
“…A similar study reported on the clinical outcomes Rehabilitation, Disability and Ageing for 32 women with breast cancer who participated in professionally facilitated and "closed" OSGs for 1.5 hours weekly over 16 weeks. 92 Improvements were made in depression and reactions to pain. Half were unable to participate due to scheduling difficulties.…”
Section: Acceptability Of Videoconferencingmentioning
confidence: 99%